Anxiety and Depression Among Chronic Obstructive Pulmonary Disease Patients in A Tertiary Care Hospital, Nepal - Roka, Tara; Aryal, Nirmala; Ghimire, Anjana; Pradhan, Subhadra; Aryal, Krishna Kumar (Journal of Kathmandu Medical College, 2018)
Background: Psychiatric co-morbidities such as anxiety and depression among patients with chronic obstructive pulmonary disease exacerbate the disease, prolong the hospital stay, increase the disease symptoms and deter the quality of life. Objective: To assess the proportion of anxiety or depression among patients with chronic obstructive pulmonary disease in a tertiary care hospital. Methodology: We carried out a cross sectional study interviewing 307 patients from a tertiary care hospital using sequential sampling technique. We used structured questionnaire and included hospital anxiety and depression scale to measure anxiety and depression. We considered a summed score of